Confirmatory Factor Analysis Intellectual Capital Disclosure LQ-45 in Indonesia - Rachmawati, Rima; Arifian Rachman, Andry; Sukma Lestari Barus, Irene (International Journal of Psychosocial Rehabilitation, 2020)
This research was conducted using confirmatory factor analysis using several indicator variables that form variables that are not measurable directly based on a theoretical basis. This study aims to confirm the latent variable indicators that makeup Intellectual Capital. That the most important part of Intellectual Capital in the form of Internal Capital is more strongly reflects the variable Intellectual Property than external capital. This shows that LQ 45 companies are advised to maintain and maintain patents, copyrights, and trademarks in their respective companies in maintaining the company’s value. Besides the Internal section, the most important thing that reflects External Capital is maintaining Company Names well compared to other variables such as brands, customers, and distribution channels so that the company can remain in the LQ 45 Company on the Indonesia Stock Exchange. So through this research, it is suggested that it is important not to commit fraud on financial statements, foster good relationships with customers, produce quality products, affordable prices and be able to meet the reach of customer needs to create loyalty in customers to consume the products produced by the Company both the tangible product nature or intangible.